AKOMODASI BUDAYA LOKAL DALAM LEGISLASI BIDANG HUKUM KELUARGA (HUKUM TENTANG HAK DAN KEWAJIBAN DALAM RUMAH TANGGA) - Yusmita Yusmita (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2017)
Abstract: This article would like to point out that some rules about family law in Indonesia are heavily influenced by the growing local culture in society. Evident from the provisions of the Marriage Act no. 1 of 1974 and the Compilation of Islamic Law is quite much influenced by the culture and conditions that developed in Indonesia and the progress of the times. This is evident from the desire to get out of the classical Jurisdiction of fiqh that puts too much of a man in a very high position, and women in disadvantaged positions. For example, the article that regulates the balance of the rights and the position of husband and wife in the household, in the association in society, and in doing legal action. The influence of local culture that is already rooted in the community appears in the statement that the husband is the head of the household and the wife is a housewife. This implies an imbalance in the position of the husband and wife, this is clearly influenced by the local culture and is supported by religious doctrine that is already integral with society, which states men are leaders for women.